RoundTable: Dealing with system shifts in Education - Rajagopal, Kamakshi; Hsiao, Ya-Ping (Amy) (Proceedings of the International Conference on Networked Learning, 2026)
Increasingly, educators, researchers, administrators and learners are recognising the complexity of the educational systems they inhabit, from the macro-level of university organisations to the micro-level of individual learning environments (Ellis & Goodyear, 2019; Damşa, 2019; Jacobson, 2010). Our educational systems thrive when students are learning and growing as human beings, to become confident citizens of our societies. However, our educational systems are also systems in flux, undergoing significant changes, caused by many factors (Jandrić et al, 2018). The societal and technological structures underpinning our systems are changing significantly due to digitalisation (Rasa, 2025). Increased globalisation has changed the nature of our student and staff population, who require adapted pedagogical approaches to facilitate learning (De Leersnyder et al., 2022). Younger generations have significantly different expectations of our educational system, in line with their values and priorities, growing up as digital-first generations (Katz et al., 2021). These shifts often bring with it foundational questions of the value of education itself, which is a slow, intentional human action seeking deep understanding in a society increasingly dominated by speed of information and action. For the people who are part of these systems and work within these systems, these system shifts present a significant problem. This problem becomes tangible in their actions (e.g. increased technology shifts such as accelerated adoption of GenAI (Nikolic et al., 2024)), their levels of motivation (e.g. significant drop in teachers/administrator numbers (UNESCO & International Task Force on Teachers for Education 2030, 2024) and mental health (teacher burnout (Thomas & Reyes, 2024)). However, there is not much support for them on how to deal with these systemic changes. Often, changes are perceived as something occurring beyond their individual or collective control, where they need to undergo the changes but cannot always direct them or choose them (Chatzipoulidis et al., 2023). A first step towards this system-level support lies in the recognition of educational systems as complex systems. But, recognising a system as complex does not equate to being able to deal with and work in complexity to achieve desired results (Chatzipoulidis et al., 2023). This is the challenge of people in education right now. In this context of system shifts, we see core problems emerging: How can teachers, educators, researchers, administrators and learners keep their focus on what is essential in the educational system, namely, that students can still learn and grow? How can they navigate a system that is constantly in flux, in confidence and with steps towards desired results? When systems need to be adapted, how can they be sure that they are adapting the system in meaningful ways? How can they make sure that the new evolving system will be balanced and adequate to the needs of our societies?